Financial and Digital Literacy as Catalysts for MSMEs’ Business Sustainability: The Roles of Product Innovation and Creativity - Surna Lastri; Marlizar Marlizar; Erlinda Erlinda; Syamsidar Syamsidar (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2025)
Purpose – This study aims to analyze the influence of financial literacy and digital literacy on the sustainability of Micro, Small, and Medium Enterprises (MSMEs) by positioning product creativity and product innovation as mediating mechanisms that explain the process of transforming knowledge-based literacy into business sustainability.Methodology – The research used a quantitative approach with a causal design. Data were collected through a structured questionnaire from 95 rattan handicraft MSME actors in Aceh Besar Regency, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) to test the direct and indirect relationships between variables.Findings – The results showed that financial literacy and digital literacy had a positive and significant effect on product creativity and product innovation. Product innovation was found to have a positive and significant effect on business sustainability and to mediate the relationships between financial literacy and business sustainability and between digital literacy and business sustainability. In contrast, product creativity had no significant effect on business sustainability and did not function as a mediator. These findings indicate that financial and digital literacy do not automatically lead to business sustainability without an implementation process that involves product innovation.Originality/Novelty – This research contributes to literature by empirically distinguishing the role of creativity as the ideation stage and innovation as the implementation stage. It shows that product innovation is a key mechanism that transforms financial literacy and digital literacy into business sustainability in traditional industry-based MSMEs.Implications – The findings emphasize the importance of integrating financial literacy and digital literacy programs with efforts to strengthen product innovation capacity. From a practical perspective, the results offer a basis for developing innovation-oriented strategies and policies for MSMEs aimed at fostering long-term business sustainability.